2016
DOI: 10.1111/apa.13592
|View full text |Cite
|
Sign up to set email alerts
|

Serum fatty acids in infants, reflecting family fish consumption, were inversely associated with allergy development but not related to farm residence

Abstract: The allergy-protective effect of farming was not linked to infant serum fatty acid composition. However, healthy infants had higher proportions of EPA in their sera, probably reflecting a family diet rich in fish, compared to subsequently allergic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 22 publications
1
20
0
2
Order By: Relevance
“…Odd-chain FA%, middle-chain FA% and, to a lesser extent, n-3 FA% in milk showed strong associations to infant PL. The stronger correlation of milk n-3 FA% to infant serum metabolites compared to milk n-6 FA% [ 15 ] in month 4 and the missing associations of long-chain saturated and mono-unsaturated FA% in milk to infant FA% were described previously [ 12 , 13 ]. Kankaanpää et al showed that serum lipid fatty acids in atopic infants did not correlate with those in maternal breast milk [ 12 ], but other trials also report strong correlations between milk trans-FA%, n-3 FA%, and n-6 FA% and infant serum FA% of PL [ 12 , 17 , 62 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Odd-chain FA%, middle-chain FA% and, to a lesser extent, n-3 FA% in milk showed strong associations to infant PL. The stronger correlation of milk n-3 FA% to infant serum metabolites compared to milk n-6 FA% [ 15 ] in month 4 and the missing associations of long-chain saturated and mono-unsaturated FA% in milk to infant FA% were described previously [ 12 , 13 ]. Kankaanpää et al showed that serum lipid fatty acids in atopic infants did not correlate with those in maternal breast milk [ 12 ], but other trials also report strong correlations between milk trans-FA%, n-3 FA%, and n-6 FA% and infant serum FA% of PL [ 12 , 17 , 62 ].…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have described the effects of maternal dietary fat intake during lactation or milk fatty acid (FA) composition on offspring health, e.g. growth [ 6 8 ], neurodevelopment [ 9 , 10 ], and the risks of atopic diseases [ 11 , 12 ] and allergy [ 13 , 14 ], but little is known on the direct effect on infant metabolism. The few association studies are limited to fatty acid percentages (FA%) of maternal milk in relation to FA% in the infant blood [ 12 , 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, delayed introduction of fish has repeatedly been associated with a higher risk of developing different atopic diseases [2229]. Accordingly, in the FARMFLORA birth cohort we found an inverse relationship between the proportions of the fish fatty acid eicosapentaenoic acid (EPA) in the sera of four-month-old infants and the risk of subsequent allergy development [30]. The proportions of EPA in the infants’ sera correlated with maternal breast milk EPA, which, in turn, correlated with the mother’s fish intake [30].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in the FARMFLORA birth cohort we found an inverse relationship between the proportions of the fish fatty acid eicosapentaenoic acid (EPA) in the sera of four-month-old infants and the risk of subsequent allergy development [30]. The proportions of EPA in the infants’ sera correlated with maternal breast milk EPA, which, in turn, correlated with the mother’s fish intake [30]. Also late introduction of eggs has been associated with an increased risk of developing asthma, allergic rhinitis, and atopic sensitization, as shown by Nwaru and coworkers [29].…”
Section: Introductionmentioning
confidence: 99%
“…Readers may also be interested in the paper by Karin Jonsson et al. who found that serum fatty acids in infants, reflecting family fish consumption, were inversely associated with allergy development, but not related to farm residence .…”
Section: Exploring the Allergic Marchmentioning
confidence: 99%